Social Distancing Violations Detection Using Iot-Based Raspberry Pi Camera - Muhammad Ilham Maulana; I Gede Putu Wirarama Wedashwara; Ariyan Zubaidi (Journal of Computer Science and Informatics Engineering (J-Cosine), 2022)
Social distancing is one of the methods used to keep yourself and others safe during a pandemic and prevent the transmission of Covid-19. With social distancing, the spread of Covid-19 can be minimized. By utilizing two tools, namely the Raspberry Pi to classify using the haar cascade classifier algorithm from data obtained from the pi camera module as a visual raspberry pi used to detect a person's body. Raspberry pi camera will start detecting using crontab unit time. If the Raspberry Pi camera detects a person who is less than one meter away, that person is said to have violated social restrictions and vice versa, the data will be stored on the Raspberry Pi which also becomes a web server. The website is used as a system user interface, Raspberry Pi camera communication uses the machine to machine (M2M) protocol which is applied to a website-based application.